2021
DOI: 10.1080/13696998.2021.1889573
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of home medication review by community pharmacists (HMR-CP) for patients with type 2 diabetes mellitus (T2DM)

Abstract: View related articles View Crossmark data Economic evaluation of home medication review by community pharmacists (HMR-CP) for patients with type 2 diabetes mellitus (T2DM)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…However, no studies were identified through forward and backward searches. Finally, 11 articles met the selection criteria and were included in the review (see Figure 1 for the PRISMA flow diagram) [ 41 , 42 , 43 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, no studies were identified through forward and backward searches. Finally, 11 articles met the selection criteria and were included in the review (see Figure 1 for the PRISMA flow diagram) [ 41 , 42 , 43 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were conducted in Bangladesh [ 48 ], China [ 47 , 52 ] including Hong Kong [ 51 ], India [ 41 , 43 , 49 ], Malaysia [ 54 ], Singapore [ 42 , 50 ], and Sri Lanka [ 53 ] with T2DM patients and participants who were at high risk of developing T2DM. Participants included in the studies were aged 5 years and above, and the average sample size of the studies was 920 participants (study samples ranged between 166 and 3539 participants).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations